School Functioning and Chronic Tension Headaches in Adolescents: Improvement Only After Multidisciplinary Evaluation. (June 2013) - Claar, Robyn Lewis; Kaczynski, Karen J.; Minster, Anna; McDonald-Nolan, Lori; LeBel, Alyssa A.
Pediatric patients with chronic tension-type headaches often experience significant school impairment. Although some improve after treatment with a neurologist, many require more comprehensive treatment. The authors examined whether school functioning and attendance improved after a multidisciplinary evaluation focusing on a return to functioning despite headaches. They also examined whether patients' headaches improved. Participants were 47 adolescents ages 12-17, most of whom had not responded to past neurological treatment. Adolescents completed the PedsQL School Functioning Scale at evaluation, 2-3 months later, and again 6 months after evaluation. Information regarding headache frequency, severity and duration, and school attendance was obtained from medical records. Using repeated measures analyses of variance, the authors found that school functioning and attendance improved significantly from evaluation to follow-up, as did headache frequency and duration. An emphasis on returning to functioning can help patients with chronic, difficult-to-treat tension-type headaches improve in their school functioning and experience fewer, shorter headaches.